A STUDY OF ACADEMIC ACHIEVEMENT IN RELATION TO MENTAL ABILITY ADJUSTMENT OF SECONDARY SCHOOL STUDENTS - Sindhe, Rajkumar Annarao; V. G. Sarpe (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article has studied the academic ability of secondary school students in urban and rural areas. Differences in their academic ability have been studied. Because of there is difference in educational availability in urban and rural areas. Which is affects the quality of education of the students living in this area. Education is the basic right of every human being. Good education is necessary to create a good future. It is a vital medium to enable everyone to reach their full potential. However, the disparity in educational attainment in urban and rural areas remains a challenge. Education provides individuals with the necessary skills and knowledge to improve their lives and contribute positively to society. However, there are significant differences in the quality and access to education between urban and rural areas. In line with this disparity, it is necessary to study the difference in educational ability of rural students due to the difference in education between urban and rural areas.